Comparative Insights of Perfume Formulations Protection in Trade Secret Laws in Indonesia, South Korea, and France - Rianda Dirkareshza; Muhammad Fauzan; Reisha Rizkia Sabila Supardi (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
The perfume industry relies heavily on innovation and unique formulations, yet in Indonesia many micro and small businesses sell inexpensive refill perfumes that imitate well-known scents, raising concerns about trade secret infringement. This study assesses the effectiveness of legal protections for perfume formulations in Indonesia, South Korea, and France through a juridical-normative, comparative, and case study approach. The findings show that Indonesia’s protections under its Trade Secret, Trademark, and Patent laws remain weak due to limited enforcement and low awareness, while South Korea’s Unfair Competition Prevention and Trade Secret Protection Act and France’s implementation of Directive (EU) 2016/943 provide stronger mechanisms for safeguarding business secrets. The study offers a comparative framework that can guide the development of a more effective trade secret regime for perfume formulations in Indonesia.